ANALISIS IMPLEMENTASI MOODLE SEBAGAI E-LEARNING DALAM PENERAPAN PEMBELAJARAN DARING (DALAM JARINGAN) DI POLITEKNIK PENERBANGAN SURABAYA - Didi Hariyanto (Universitas Sebelas Maret, 2021)
This study aims to analyze the implementation of Moodle as e-learning in the online learning application at the Aviation Polytechnic of Surabaya. The research method employed the descriptive qualitative method. The sample in this study consisted of 46 cadets from the Aviation Communication Study Program Batch V Alpha and Bravo at Aviation Polytechnic of Surabaya. This research was carried out from March 2020 to June 2020 at the Aviation Polytechnic of Surabaya. Data were collected using observation, questionnaires, interviews, and literature studies. The data obtained through questionnaires were then analyzed utilizing descriptive analysis techniques with percentages. The results of the optimal level of Moodle as e-learning in the online learning application from users, namely cadets, reached 79.56% for the user satisfaction aspect, with a good category. From the usability aspect, it got 73.61%, with enough category. From the graphic design aspect, it attained 56.74%, with enough category. The navigation aspect reached 76.95% in the good category, while the content aspect obtained 84.34% in the good category. Overall, the response of the VA and VB Aviation Communication cadets obtained 74.24%, with enough category. Thus, it can be concluded that Moodle as e-learning in the online-based learning application at the Aviation Polytechnic of Surabaya was not fully optimal since it was still in enough category. For this reason, it needs to be further developed from the usability aspect, graphic design, and additional features, such as video on demand and video streaming.